2020
DOI: 10.1093/comnet/cnaa049
|View full text |Cite
|
Sign up to set email alerts
|

Does meditation lead to a stable mind? Synchronous stability and time-varying graphs in meditators

Abstract: The dynamical approach represents a new branch in the understanding of functional brain networks. Using simple indices to represent time connectivity and topological stability, we evaluated the hypothesis of increased brain stability during the meditative state in comparison to the relaxation state. We used a new way to consider the time evolution of synchronization patterns in electroencephalography (EEG) data. The time-varying graph approach and the motif synchronization method were combined to build a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 132 publications
1
9
0
Order By: Relevance
“…These results are in line with previous studies showing a reduced spatiotemporal dynamic across the whole-brain functional network in DOC patients (A. Demertzi et al, 2019;Hannawi et al, 2015;López-González et al, 2021;Schiff et al, 2014), deep sleep (Horovitz et al, 2009;Ipiña et al, 2020;Jobst et al, 2017;Schartner et al, 2017), and meditation (Escrichs et al, 2019;Toutain et al, 2021) compared to normal resting state.…”
Section: Revealing Susceptibility and Information Encoding Capability Using Whole-brain Modellingsupporting
confidence: 93%
“…These results are in line with previous studies showing a reduced spatiotemporal dynamic across the whole-brain functional network in DOC patients (A. Demertzi et al, 2019;Hannawi et al, 2015;López-González et al, 2021;Schiff et al, 2014), deep sleep (Horovitz et al, 2009;Ipiña et al, 2020;Jobst et al, 2017;Schartner et al, 2017), and meditation (Escrichs et al, 2019;Toutain et al, 2021) compared to normal resting state.…”
Section: Revealing Susceptibility and Information Encoding Capability Using Whole-brain Modellingsupporting
confidence: 93%
“…The copyright holder for this preprint this version posted June 10, 2021. ; https://doi.org/10.1101/2021.06.10.447903 doi: bioRxiv preprint et al, 2019). Similar evidence comes from the work conducted by Toutain et al (2020), in which they investigated topological stability across relaxation state and meditation in experienced meditators using the electroencephalogram (EEG). The authors demonstrated an increase in stability of global topological patterns during meditation compared to relaxation state (Toutain et al, 2020).…”
Section: Introductionmentioning
confidence: 62%
“…Similar evidence comes from the work conducted by Toutain et al (2020), in which they investigated topological stability across relaxation state and meditation in experienced meditators using the electroencephalogram (EEG). The authors demonstrated an increase in stability of global topological patterns during meditation compared to relaxation state (Toutain et al, 2020). Nonetheless, these phenomenological studies cannot by nature provide a mechanistic explanation about how long-term meditation practice shapes the global spatio-temporal BOLD structure via the underlying interregional connections, which instead requires a model-based approach.…”
Section: Introductionmentioning
confidence: 62%
“…Similar evidence comes from the work conducted by Toutain et al (2020), in which they investigated topological stability across relaxation state and meditation in experienced meditators using the electroencephalogram (EEG). The authors demonstrated an increase in stability of global topological patterns during meditation compared to relaxation state (Toutain et al, 2020).…”
Section: Introductionmentioning
confidence: 62%
“…At the same time, they found that meditation appears to be characterized as a state of reduced information processing, indicating a switch to a less complex regime compared to the resting state (Escrichs et al, 2019). Similar evidence comes from the work conducted by Toutain et al (2020), in which they investigated topological stability across relaxation state and meditation in experienced meditators using the electroencephalogram (EEG). The authors demonstrated an increase in stability of global topological patterns during meditation compared to relaxation state (Toutain et al, 2020).…”
Section: Introductionmentioning
confidence: 65%